Bridging Feminist Psychology and Open Science: Feminist Tools and Shared Values Inform Best Practices for Science Reform. (December 2021) - Matsick, Jes L.; Kruk, Mary; Oswald, Flora; Palmer, Lindsay
Feminist researchers have long embraced the challenging, dismantling, and reimagining of psychology, though their contributions to transforming psychological science remain largely overlooked in the mainstream open science movement. In this article, we reconcile feminist psychology and open science. We propose that feminist theory can be leveraged to address central questions of the open science movement, and the potential for methodological synergy is promising. We signal the availability of feminist scholarship that can augment aspects of open science discourse. We also review the most compelling strategies for open science that can be harnessed by academic feminist psychologists. Drawing upon best practices in feminist psychology and open science, we address the following: generalizability (what are the contextual boundaries of results?), representation (who is included in research?), reflexivity (how can researchers reflect on who they are?), collaboration (are collaborative goals met within feminist psychology?), and dissemination (how should we give science away?). Throughout each section, we recommend using feminist tools when engaging with open science, and we recommend some open science practices for conducting research with feminist goals.